The Combined Principles of Local History: Indonesian and Western Perspectives - Ilyas, Yusran; Sholihah, Rianti; Wijayanti, Divani Truna (Analisis Sejarah, 2025)
This article introduces a more comprehensive principle of local history by combining Indonesian and Western perspectives, each of which emerged from different backgrounds and produced distinct theorems. In Indonesia, local history emerged in the post-independence era to reconstruct local experiences neglected in national historical narratives. Similarly, in the West, local history developed as a critique of historiography focusing solely on prominent figures and political events. Both approaches share the aim of narrating the experiences of marginalised groups. Integrating Indonesian and Western perspectives has produced five key principles: heterogeneity, populism, multidisciplinarity, multiperspectivity, and a combination of phenomenological and objective approaches. This principle emerged through four stages of research: heuristics, source criticism, interpretation, and historiography.